English Language Teachers’ Wellbeing in the Workplace: A Case Study in Türkiye - Bilhan, Arzu; Akcayoglu, Meryem (My University, 2025)
This qualitative study drew on Seligman's PERMA, Positive Emotion, Engagement, Relationships, Meaning, and Accomplishments, model (2011) to examine the wellbeing of English language teachers at work in the schools managed by the Ministry of National Education. It also examined factors affecting teachers' wellbeing in their institutional environments. The perceptions of teachers about how their jobs and workplaces affect their general wellbeing were also explored. The study was conducted in Elazığ, a city in Türkiye's Eastern Anatolia region. 53 EFL teachers working in public or private schools participated in this study. Semi-structured interviews and open-ended survey questions were used to gather the data. To reach as many English language teachers as feasible in this city, snowball sampling was used. The data were analysed using both inductive and deductive Thematic Analyses. Firstly, data were analysed deductively, and the PERMA model was used as a theme to answer the first research question. For the second and third research questions, data were analysed inductively to find emerging themes. The PERMA findings show that teachers are in a high state of wellbeing. They stand out for having positive emotions, good relationships, powerful meanings, and pleasure with their professional accomplishments. Student motivation and success, approval and support, and social relationships were discovered to be the three main themes that have an impact on teachers' wellbeing. The results also show that English language teachers believe their profession and workplace have a substantial impact on their general wellbeing, either positively or adversely.
Keywords: PERMA; Positive pyschology; teacher wellbeing; positive and negative emotions